2020
DOI: 10.47339/ephj.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Individual emergency preparedness survey among Canadians in Lower Mainland, BC

Abstract: Background: BC residents are prone to natural disasters and emergencies such as earthquakes and prolonged power outage due to severe weather and flooding. To minimize and mitigate the impacts, individuals should prepare in advance for any potential emergencies. There are studies showing only half of the Canadians, in general, are well prepared. Concrete evidence of factors affecting individual’s emergency preparedness are not clear. Therefore, this research study aims to investigate the association between BC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This finding is supported by several studies that have also suggested that homeowners are more likely to be prepared for a household emergency than renters. [27][28][29] Some reasons for this might include: (1) better financial resources and access to funds than renters, (2) higher income, (3) greater interest in protecting home and family assets, and (4) more concrete ties to local communities, which could help them learn about risks to their area. 30 This study also found that higher levels of education and higher household income were associated with increased HEP scores.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by several studies that have also suggested that homeowners are more likely to be prepared for a household emergency than renters. [27][28][29] Some reasons for this might include: (1) better financial resources and access to funds than renters, (2) higher income, (3) greater interest in protecting home and family assets, and (4) more concrete ties to local communities, which could help them learn about risks to their area. 30 This study also found that higher levels of education and higher household income were associated with increased HEP scores.…”
Section: Discussionmentioning
confidence: 99%